2018
DOI: 10.1590/1517-869220182402175290
|View full text |Cite
|
Sign up to set email alerts
|

Walking With Blood Flow Restriction Improves the Dynamic Strength of Women With Osteoporosis

Abstract: Introduction: Improving strength levels is important to women with osteoporosis. Resistance and aerobic exercise are effective means of reaching this goal; however, the use of low-load exercises with blood flow restriction is an alternative to traditional methods of exercise to achieve the same strength gains in this population. Objective: To analyze the chronic effects of aerobic and resistance training combined with blood flow restriction on the maximal dynamic strength (MDS) of women with osteoporosis. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…1 ). From the remaining 270 studies, 251 were excluded through title screening and abstract assessment, while 19 studies were excluded following full-text reading, and one study was excluded as SMD could not be calculated from the reported data [ 34 ]. Consequently, a total of seven studies [ 14 – 18 , 35 , 36 ] were included in the present meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…1 ). From the remaining 270 studies, 251 were excluded through title screening and abstract assessment, while 19 studies were excluded following full-text reading, and one study was excluded as SMD could not be calculated from the reported data [ 34 ]. Consequently, a total of seven studies [ 14 – 18 , 35 , 36 ] were included in the present meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, following a shorter BFR walking intervention (i.e., 6 weeks), Abe et al (2) reported increases in isometric (11%) and isokinetic (7-16%) strength of the knee extensors and flexors, with no change reported in a no exercising control group. Pereira et al (30) (11).…”
Section: Effects Of Blood Flow Restriction Walking On Cardiovascular ...mentioning
confidence: 99%
“…Pereira et al (30) investigated the effects of BFR interventions (12 weeks duration) on dynamic muscle strength in older women with osteoporosis. The authors reported a 22% increase in leg strength in a group that performed BFR walking, whereas there was no change in leg strength for a no exercise control group.…”
Section: Introductionmentioning
confidence: 99%
“…Walking is considered a pain-free activity that does not require recovery time nor special equipment or specific training, which makes it a recommended form of physical activity for those in rehabilitation from illness or injury. Walking is often recommended for elders suffering from osteoporosis (Pereira Neto et al, 2018). Walking has also proven to be a safe activity for those recovering from cardiovascular diseases (Martinez et al, 2009;Novaković et al, 2019) or chronic musculoskeletal pain (O'Connor et al, 2015).…”
Section: Walking and Healthmentioning
confidence: 99%